2022
DOI: 10.1080/03019233.2022.2099696
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of inclusions with cerium addition and effects of C-containing rare earth inclusions on the toughness of ultra-high-strength structural steel

Abstract: Ultra-high strength structural steels with Ce (cerium) content of 0, 0.0367, 0.0559 and 0.0792 wt.% respectively are prepared to study the effect of Ce addition on inclusions and the toughness of ultra-high-strength steel. The results show that the 0.0367 wt.% Ce can refine the size of oxides or sulfides to about 1 μm and improve the inclusion morphology to spherical, resulting in improved toughness of L-Ce steel. The number of inclusions in the H-Ce steel increases sharply, mainly due to the precipitation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Specifically, the balance between the Ce 2 O 3 -containing refining slag and the molten steel-containing aluminum will lead to a small amount of cerium being dissolved into the molten steel. This rare earth element can perform a vital role in purifying, modifying, and micro-alloying steels [138], modifying the inclusions [139][140][141][142], refining the solidification structure [143], and improving the performance [144][145][146] of RE steels. The effects of rare earth elements on the modification of inclusions have been widely studied, both in lab experiments and within industrial scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the balance between the Ce 2 O 3 -containing refining slag and the molten steel-containing aluminum will lead to a small amount of cerium being dissolved into the molten steel. This rare earth element can perform a vital role in purifying, modifying, and micro-alloying steels [138], modifying the inclusions [139][140][141][142], refining the solidification structure [143], and improving the performance [144][145][146] of RE steels. The effects of rare earth elements on the modification of inclusions have been widely studied, both in lab experiments and within industrial scale production.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the solidification structure was refined, and a large number of small Ce 2 O 2 S inclusions promoted the nucleation of the solidification process. At the same time, the evolution path of inclusions after adding Ce was studied: Al 11 O 18 Ce→CeAlO 3 →Ce 2 O 3 →Ce 2 O 2 S. Y. Jiang [29] prepared ultra-high-strength structural steel with a Ce content of 0, 0.0367, 0.0559, and 0.0792 wt.% and studied the effects of Ce addition on inclusions and the toughness of ultra-high-strength steel. The results showed that 0.0367wt.% Ce can refine the size of oxides or sulfides to about 1 µm, improve the morphology of inclusions to create a spherical shape, and, thus, improve the toughness of L-Ce steel.…”
Section: Thermodynamic Analysis Of Inclusion Modifications In Gcr15 B...mentioning
confidence: 99%
“…In addition, small amounts of rare earth elements are dissolved in microalloyed steels by vacancy diffusion, occupying lattice cross-section points. In manganese steels, rare earth elements interact with carbon atoms and influence the phase transformation and precipitation of carbides [14][15][16]. Rare earth atoms with large diameters and high distortion energies tend to polarize at the ferrite-carbide interface [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In manganese steels, rare earth elements interact with carbon atoms and influence the phase transformation and precipitation of carbides [14][15][16]. Rare earth atoms with large diameters and high distortion energies tend to polarize at the ferrite-carbide interface [16,17]. The microalloying effect of rare earths in steel is becoming increasingly significant as the cleanliness of steel continues to improve.…”
Section: Introductionmentioning
confidence: 99%